Ferroelectric and ferromagnetic properties of (x)BaTiO3+(1-x)Ni0.94Co0.01Cu0.05Fe2O4 composite - Devan, R. S.; Deshpande, S. B.; Chougule, B. K. (Journal of Physics D-Applied Physics, 2007)
A group of elastically coupled ferroelectric and ferrite composites with the general formula (x) BaTiO3 + (1 - x) Ni0.94Co0.01Cu0.05Fe2O4 (where x = 0.85, 0.70 and 0.55) was prepared by the standard ceramic reaction method. The x-ray diffraction pattern of the composite reveals a spinel phase formation for the ferrite and perovskite phase formation for the ferroelectric phase without any other phase. The SEM micrographs were taken to determine the average grain size. The sintered composites exhibit typical hysteresis loops at room temperature. The effect of constituent phase variation on the hysteresis behaviour and the dielectric properties was examined. The parameters such as spontaneous polarization (P-s), breakdown voltage (E-b) and saturation magnetization (M-s) of the composites vary with the ferroelectric/ ferrite content. The temperature dependence of dielectric behaviour at a frequency of 1 kHz was also studied. With increasing content of BaTiO3, the dielectric constant increases and the Curie temperature decreases.